Single-cell analysis of transcription factor regulatory networks reveals molecular basis for subtype-specific dysregulation in acute myeloid leukemia. Issue 2 (April 2022) - Sun, Ruixia; Sun, Lina; Xie, Xiaowei; Li, Xuan; Wu, Peng; Wang, Lu; Zhu, Ping
Abstract : Abstract: Highly heterogeneous acute myeloid leukemia (AML) exhibits dysregulated transcriptional programs. Transcription factor (TF) regulatory networks underlying AML subtypes have not been elucidated at single-cell resolution. Here, we comprehensively mapped malignancy-related TFs activated in different AML subtypes by analyzing single-cell RNA sequencing data from AMLs and healthy donors. We first identified six modules of regulatory networks which were prevalently dysregulated in all AML patients. AML subtypes featured with different malignant cellular composition possessed subtype-specific regulatory TFs associated with differentiation suppression or immune modulation. At last, we validated that ERF was crucial for the development of hematopoietic stem/progenitor cells by performing loss- and gain-of-function experiments in zebrafish embryos. Collectively, our work thoroughly documents an abnormal spectrum of transcriptional regulatory networks in AML and reveals subtype-specific dysregulation basis, which provides a prospective view to AML pathogenesis and potential targets for both diagnosis and therapy.